Reducing insulin prescription errors in hospital: more stick than carrot?. (November 2013) - Hamilton, P; Nation, M; Penfold, S; Kerr, D; Richardson, T
Abstract: People with diabetes are more likely to be admitted to hospital and have longer stays in hospital than people without diabetes. Data from the National Diabetes Inpatient Audit suggest that people with diabetes experience avoidable prescription errors such as wrong insulin, incorrect doses and omitted doses. These errors result in increased length of stay and harm to the patient. Many of the errors occur due to deficiencies in knowledge. Our aim was to reduce prescription errors and improve health care professionals' knowledge by introducing the following initiatives: (1) redesign of the diabetes prescription chart; and (2) implementing a root cause analysis prescription error pathway which involves a targeted approach to education for the individual who made the error. Following introduction of the changes to the insulin prescription chart, data from our participation in the National Diabetes Inpatient Audit reported that prescription errors were reduced from 65% to 14% and management errors from 40% to 14% from 2009 to the beginning of 2012. The results of the internal audit during 2012–2013 demonstrated a further reduction in prescription/management errors to 2% following the introduction of the root cause analysis pathway. The changes have demonstrated a significant reduction in prescription errors and an increased awareness of diabetes following the targeted approach to education. Copyright © 2013 John Wiley & Sons.